Very massive stars : mass determination and fate / Norhasliza binti Yusof - Yusof, Norhasliza (2012)
The first generation of stars is thought to have been very massive (150-300 M) and produces pair creation supernovae (PCSNe) at the end of their life. However, the chemical signature of PCSNe is not observed in extremely metal poor stars (e.g. Umeda & Nomoto, 2002) and it raises the following questions: Were stars born less (or more massive) than the mass range expected to lead to the PCSNe? Or is mass loss too strong during the evolution of these stars and prevented them from retaining enough mass to produce PCSNe? The discovery of very massive stars (VMS, M> 100 M) in the Milky Way and LMC (Crowther et al., 2010) shows that VMS can form and exist. The observation of PCSN candidates (SN 2006gy & SN 2007bi) also seems to indicate that such supernovae (SNe) may occur. Mass loss plays a crucial role in the life of VMS since the star will only die as a PCSN if the star retains a high mass throughout its life. In this thesis, we shall describe the dependence of VMS evolution on metallicity and present stellar evolution models at various metallicities, including the eects of mass loss and rotation. Based on our models, we will give our predictions concerning the fate of these VMS, either a PCSN or supernova Type Ic (SN Ic) as a function of metallicity and mass loss rate prescriptions used. Our models that predict the star will end up as PCSN are models at LMC metallicity with mass around 500 M and rotating SMC metallicity models with mass 120 < M < 280. Other than that it will die as a black hole or a core-collapse supernova. We also study the impact of the updated neutrino energy loss from Itoh et al. (1996) that supersedes the neutrino energy loss from Itoh et al. (1989) which has been used in the Geneva stellar evolution code. Neutrino energy loss is an important process in the evolution of advanced stages of massive stars since most of the energy loss is through the neutrino processes. From our study, the VMS do not have any signicant eects when we update the neutrino energy loss. This is due to the prominent process in neutrino energy loss which is photoneutrino process that remains unchanged in Itoh et al. (1996). Finally we apply an updated nuclear reaction rates using WKB method for 12C(p, )13N, 15N(p, )16O and 16O(p, )17F in the CNO cycle. Evolution of massive and very massive stars are studied and we nd the new reaction rates inuence the surface and central abundances of 12C in these stars.